FRK inhibits glioblastoma progression via phosphorylating YAP and inducing its ubiquitylation and degradation by Siah1. Issue 12 (20th June 2022) - Wang, Yan; Wang, Kai; Fu, Jiale; Zhang, Yu; Mao, Yufei; Wang, Xu; Wang, Xiang; Yu, Rutong; Zhou, Xiuping
Abstract: Background: We previously report that yes-associated protein (YAP), the core downstream effector of Hippo pathway, promotes the malignant progression of glioblastoma (GBM). However, although classical regulatory mechanisms of YAP are well explored, how YAP is modulated by the Hippo-independent manner remains poorly understood. Meanwhile, the nonreceptor tyrosine kinase Fyn-related kinase (FRK), which exhibits low expression and possesses tumor suppressor effects in GBM, is reported to be involved in regulation of protein phosphorylation. Here, we examined whether FRK could impede tumor progression by modulating YAP activities. Methods: Human GBM cells and intracranial GBM model were used to assess the effects of FRK and YAP on the malignant biological behaviors of GBM. Immunoblotting and immunohistochemistry were used to detect the expression of core proteins in GBM tissues. Co-immunoprecipitation, proximity ligation assay, luciferase assay and ubiquitination assay were utilized to determine the protein–protein interactions and related molecular mechanisms. Results: The expression levels of FRK and YAP were inversely correlated with each other in glioma tissues. In addition, FRK promoted the ubiquitination and degradation of YAP, leading to tumor suppression in vitro and in vivo. Mechanistically, FRK interacted with and phosphorylated YAP on Tyr391/407/444, which recruited the classical E3 ubiquitin ligase Siah1 to catalyze ubiquitination and eventually degradation of YAP. Siah1 is required for YAP destabilization initiated by FRK. Conclusions: We identify a novel mechanism by which FRK orchestrates tumor-suppression effect through phosphorylating YAP and inducing its ubiquitination by Siah1. FRK-Siah1-YAP signaling axis may serve as a potential therapeutic target for GBM treatment.